DEVELOPMENT OF INCLUSIVE EDUCATION IN THE CARPATHIANS - Matveievа, Nataliia (Mountain School of Ukrainian Carpaty, 2020)
The article reveals the main ways of introduction and development of inclusion in Prykarpattia; features of educational inclusion on the basis of the analysis of activity of educational institutions of preschool, initial and average link are characterized; the purpose, tasks and directions of development of inclusive infrastructure of the regional center are singled out. The functional and semantic characteristics of the practical work of teachers of educational institutions on the way to creating an inclusive environment are studied, generalized and revealed; processed and analyzed statistical data on the inclusion of persons with special educational needs in mass educational institutions; identified the main gaps and omissions of this process at the present stage; further prospects for development are outlined.